UNDERSTANDING THE CURRENT TREND OF HIJRAH: BETWEEN SELF-EXISTANCE AND RELIGIOUS UNDERSTANDING - Dian Ayuningtyas; Tuti Hidayati; Inayatillah; Putri Rahmawati (Risalah, Jurnal Pendidikan dan Studi Islam, 2022)
Hijrah is a great momentum in the history of da’wa Islam and was designated as the first year of Islamic calendar. Although it was initially associated with process of migration, the interpretation of hijrah is not limited to simply as moving from one place to another. In fact, it is referred to a significant milestones as a process of migrating or transforming to a better situation or a better self. These days, hijrah has become a phenomenal trend that is not only popular among those who are active in following Islamic group discussions but also among the youths who are the social media worshipers. Hijrah is viewed as the process of self-transformation and as an effort to practice all Islamic teachings performed by Rasulullah in daily life. During the process, however, the substantial values and the real meaning of hijrah are often considered missing. Rather than the change of attitudes and characters, it is often represented merely as changing physical appearances or ways of speaking. This paper is aimed to revisit the concept of hijrah in Islam and analyze its values and meanings within the current developing social phenomena. The study is conducted in a qualitative descriptive approach, and data collection was performed through literature study. The result shows that the dynamic practice of Islam highlights the current concept of hijrah. The core values in this self-transformation is to leave all the bad habits, to be more religious, and to embrace the modernity without compromising the faith.